The Influence Of Product Prices And Reviews Purchase Decisions On E-Commerce Shopee (Case Study in the Community of Bandar Lampung City) - Audy Frisca Rosa; Farida Efriyanti (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to identify the influence of price and product reviews on purchasing decisions in the Shopee e-commerce case study in the Bandar Lampung community. This research uses quantitative methods using a sample of 100 respondents calculated using the Cochran formula. The analysis techniques used in this research are validity and reliability tests, classical assumption tests, multiple liner regression tests, hypothesis tests and coefficient of determination tests, data were processed using the IBM SPSS 25 (2023) application. Based on the results obtained in this research, price has a positive and significant effect on purchasing decisions, product reviews have a positive and significant effect on purchasing decisions. Then, together, price and product reviews have a positive and significant influence on purchasing decisions. Prices and product reviews can be an effective approach for sellers to influence purchasing decisions.